Children's experiences with Child Protection Services: A synthesis of qualitative evidence. (June 2020) - Wilson, Samita; Hean, Sarah; Abebe, Tatek; Heaslip, Vanessa
Highlights: A systematic review and qualitative evidence synthesis of children's emic experiences. Children need emotional as much as physical safety, especially during CPS investigation. Children in care want to be seen as 'normal' rather than 'vulnerable' and 'bad'. CPS policies are adopting UNCRC; the protectionist discourse prevails in practice. Children in CPS are not a homogenous group, this should reflect in research as well. Abstract: Background: Research shows that young adults, previously in contact with Child Protection Services (CPS) often have lower overall wellbeing when compared to their peers in the general population. To redress this balance and fulfil children's right to receive good quality and child-centred services, the child's lived experience of the CPS processes and interventions must be better understood. There is research with children about specific aspects of CPS, such as experiences of investigation, out-of-home care, end of intervention and participation. Yet, there is no available synthesis of the literature that would provide a general overview of children's lived experiences of these services. Objective: The aim of this review was to comprehensively identify, synthesise and analyse the current empirical research that explored children's overall experiences of Child Protection Services. Method: This is a systematic review and qualitative evidence synthesis of primary studies. A systematic search was conducted using five databases related to social sciences and social work for relevant qualitative publications in English. Using PRISMA, 39 studies were included in this review. A qualitative evidence synthesis was carried out, which entailed extracting, synthesising and thematic analysis of text from the findings section of the included studies. Results: Most of the literature focused on the perceptions of children in out-of-home care. Four main themes emerged that captured these subjective experiences: children described the processes of coming in contact with CPS, their experiences of the CPS intervention or services, their perceptions of the outcomes of the intervention and lastly their perceptions of self, social identity and stigmatisation. Discussion and Conclusion: This review concludes that, from the perspective of the child, clear, understandable and comprehensive information about the CPS process is required so that they can assert their right to participation and protection. Being in CPS is an emotional experience for them, thus emotional as much as physical safety, is needed. A sense of belongingness and self-actualization are as important for children's wellbeing as food and shelter. This knowledge should be considered in practice to improve both short and long-term outcomes for children in contact with the CPS.